Innovation and Creativity of Islamic Religious Education Teachers in Utilizing Digital-Based Learning Media - Kharismatunisa, Ilma (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to (1) examine the learning media in teaching Islamic Religious Education, (2) discover the innovation of Islamic Religious Education teachers in utilizing digital-based learning media, (3) unveil the creativity of Islamic Religious Education teachers in developing learning material (4) and imply Religious Education teacher’s innovation and creativity in utilizing digital learning media. The research utilizes a qualitative study with a literature-based approach (Library Research). The research data consists of information regarding the innovation and creativity of Islamic Religious Education teachers in utilizing digital-based learning media. The data was obtained from various sources such as books, scholarly journals, academic works, relevant literature, and other publications. The data collection technique employed in this research is documentation and analysis using content analysis. The findings revealed that digital-based learning media in Islamic Religious Education includes internet-connected animated videos, Google Classroom as an online learning platform, Quizziz as an online game, and WhatsApp as a social media application. Furthermore, innovation by Islamic Religious Education teachers in utilizing digital learning media includes the use of digital learning media in the form of animated videos for teaching Islamic concepts. The implementation of this digital-era teaching model was supported by an internet network, blended learning, and innovative digital learning media that created a more engaging, interactive, and relevant learning environment. Furthermore, it discloses the creativity of Islamic Religious Education teachers in applying digital-based learning through digital video animations using Google Classroom as a digital learning platform and utilizing WhatsApp for instructional purposes. The study's implications suggest that utilizing digital learning media has significant impacts on boosting the quality of learning Islamic Religious Education, enhancing student motivation and interest, improving accessibility to learning resources, and increasing the effectiveness of assessment and feedback.